Fair Pay, Fair Play : Aligning Executive Performance and Pay. - Ferracone, Robin A. (John Wiley & Sons, 2010)
A timely look at how to evaluate and determine executive pay. Recognized as the leading expert on executive compensation, Robin Ferracone combines her own 20 years of experience with interviews with executives and compensation committees to provide a clear examination of and guidance on determining pay packages, actions, and designs. and Over the past 25 years, the author has created a database of executive pay across 44,000 companies, broken down by company performance, company revenue and industry. Using this data, the author provides boards and individuals evaluating executive pay with the.